Assessing the Factorial Complexity of the Verbal Aggressiveness Scale - Croucher, Stephen M. (2013)
This study examined the best-fitting factor structure for the Verbal Aggressiveness Scale (VAS). Infante and Wigley’s scale is often scored as unidimensional. However, factor analytic studies have offered evidence that the scale is multidimensional. This study (N = 185) adopted a crossvalidation approach to factor analysis to ascertain the best-fitting factor structure for the VAS. Half of the data was subjected to exploratory factor analysis and the other half was then validated through confirmatory factor analysis. Results revealed a 15-item, two-factor model, with one factor measuring ego-supportive communication and the other measuring aggression. Theoretical and methodological implications are discussed.